2015
DOI: 10.4038/tar.v26i1.8083
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of evaporative water cooled (EWC) grinding method for chilli (Capsicum annum L.)

Abstract: ABSTRACT:The application of low temperature grinding shows promising pathway to produce higher quality ground product in terms of flavour and volatile oil retention of spices. 49.19 ± 0.99 (L*), 17.35 ± 1.62 (a*), 23.38 ± 1.29 (b*) and 47.52 ± 1.74 (L*), 18.38 ± 0.14 (a*) and 26.93 ± 0.68 (b*). This study revealed that the water can be effectively used as a coolant for reducing temperature rise during grinding in order to preserve the quality of chilli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…energy imparted to the material, only 1% energy is utilized in loosening the bond between particles, whereas almost 99% of input energy is being utilized in the heat generation resulting the rise in the temperature of the ground product (Bandara et al, 2014). During grinding of spices, the temperature of a product rises to a level in the range of 42-95 ºC (Pruthi and Misra, 1963;Singh and Goswami, 1997).…”
Section: Article Infomentioning
confidence: 99%
See 2 more Smart Citations
“…energy imparted to the material, only 1% energy is utilized in loosening the bond between particles, whereas almost 99% of input energy is being utilized in the heat generation resulting the rise in the temperature of the ground product (Bandara et al, 2014). During grinding of spices, the temperature of a product rises to a level in the range of 42-95 ºC (Pruthi and Misra, 1963;Singh and Goswami, 1997).…”
Section: Article Infomentioning
confidence: 99%
“…The cell damage produced in grinding further has an adverse effect on the protein, amino acids and vitamins (Hanser, 1968). Thus, thermal damage is one of the main limitations of the conventional milling process (Bandara et al, 2014).…”
Section: Article Infomentioning
confidence: 99%
See 1 more Smart Citation
“…Grinding is the most power consuming operation. Only 1% of the energy imparted into the material is utilized during grinding in loosening the bond between particles, whereas almost 99% of input energy is dissipated as heat, raising the temperature of the ground product [2]. Stone mills generate considerable heat due to friction.…”
Section: Introductionmentioning
confidence: 99%
“…Jefferes and Rubenthaler (1977) found that as mill temperature increased due to friction and use, flour yield decreased. Thus, thermal damage is one of the main limitations of the conventional milling process [2]. Malkin and Guo (2007) suggested that a better product could be obtained by reducing the temperature of the two rubbing surfaces.…”
Section: Introductionmentioning
confidence: 99%